Aplicación de la información de la vida útil en la planeación y diseño de proyectos de edificación - Hernández Moreno, Silverio (Acta Universitaria, 2011)
This paper presents a review article concerning to service life planning in the process of building design aimed to architects, builders and developers. This article is based on international standardization concerning to ISO/TC59 /SC14 “Design Life” and ISO 15686 “Service life of buildings”. The aim of the paper is to explain the application and use of service life information of building components and materials during planning and design phases of the project. This work is the result of literature review of specialized information concerning to Life cycle design, Building service life planning and sustainable architecture. We conclude that the information of service life, performance and durability of building components is very useful during the building design process, from the pre-design stage to design and construction stages because it does predict and reduce environmental impacts that project may cause.
Keywords: Array; Array; Array; Array; Array